Faktor-Faktor yang Berhubungan dengan Status Gizi pada Lansia di Desa Mongolato Kecamatan Telaga Kabupaten Gorontalo - Elsa U. Ahmad; Hamna Vonny; Rini Asnawaty (Jurnal Pengabdian Ilmu Kesehatan, 2026)
The elderly are an age group that is vulnerable to various health problems, one of which is nutritional status. This condition is influenced by various physical and psychological factors. This study was conducted to determine the relationship between depression, physical activity, and diet with nutritional status in the elderly in Mongolato Village, Telaga District, Gorontalo Regency. The approach used was quantitative with a descriptive correlational design and cross-sectional method, a sample of 75 respondents was taken using a total sampling technique. Nutritional status was measured using (BMI), while depression, physical activity, and diet were measured using a questionnaire. The analysis was carried ouf univariately and bivariately using the Spearman rank correlation test. The results of the analysis showed that the elderly had a normal nutritional status, namely 35 respondents (46.7) did not experience depression, namely 50 respondents (66.7%) had moderate to high physical activity, a good diet namely 53 respondents (70.7%) concluded in this study there was a significant relationship between depression, physical activity, diet with the nutritional status of the elderly (p <0.05).